State versus Community: A Confusing Policy Discourse in Nepal’s Forest Management - Timsina, Netra; Paudel, Naya Sharma (Journal of Forest and Livelihood, 2003)
The issue of forest governance in Nepal is highly dominated by the state versus community discourse, dividing intellectuals, professionals and practitioners into two ideological camps. We argue that this debate is theoretically weak and practically less useful, as it fails to take into account the semi-feudal and hierarchical Nepalese communication structure. This divide has largely undermined the internal differentiations both within the state and community organizations, assuming them to be homogenous and monolithic. It is shown how this dichotomy and the resultant policy processes have strengthened the alliances between local elite, bureaucrats and politicians, further marginalizing the poor and disadvantaged forest users. It suggests that the focus of the discourse should be on the complex interactions among the social actors crosscutting state- community divide.